Pembinaan Olahraga Karate di Dojo Ojeroles Karate Team Kabupaten Blitar - Nurdiah Indahsari Suhariyanto (COMSERVA : Jurnal Penelitian dan Pengabdian Masyarakat, 2023)
Karate is a martial arts sport originating from Japan, and is a body contact sport that involves physical touch. This activity serves to provide additional material to Karate athletes in the Ojeroles Karate Team Dojo. This activity also aims to get to know, know, and identify the conditions of the school environment or training ground.